2012
DOI: 10.1371/journal.pone.0046571
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Activates HIF-1 in Oxidative but Not in Warburg-Phenotype Human Tumor Cells

Abstract: Cancer can be envisioned as a metabolic disease driven by pressure selection and intercellular cooperativeness. Together with anaerobic glycolysis, the Warburg effect, formally corresponding to uncoupling glycolysis from oxidative phosphorylation, directly participates in cancer aggressiveness, supporting both tumor progression and dissemination. The transcription factor hypoxia-inducible factor-1 (HIF-1) is a key contributor to glycolysis. It stimulates the expression of glycolytic transporters and enzymes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
228
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(246 citation statements)
references
References 58 publications
15
228
0
3
Order By: Relevance
“…23) Recently, it was reported that lactic acid activated HIF-1 and triggers tumor angiogenesis and tumor growth. 24) Our results showed that PKC activation modulated glycolysis and lactic acid levels in RD cells. Collectively, we suggest that PKC inhibitor may lead to reduction in the chance of the rhabdomyosarcoma by inhibition of glycolysis and production of lactic acid.…”
Section: Regulation Of the Expression And Activity Of Lactic Acid Metmentioning
confidence: 50%
“…23) Recently, it was reported that lactic acid activated HIF-1 and triggers tumor angiogenesis and tumor growth. 24) Our results showed that PKC activation modulated glycolysis and lactic acid levels in RD cells. Collectively, we suggest that PKC inhibitor may lead to reduction in the chance of the rhabdomyosarcoma by inhibition of glycolysis and production of lactic acid.…”
Section: Regulation Of the Expression And Activity Of Lactic Acid Metmentioning
confidence: 50%
“…Whether lac tate is an in di rect in di ca tor of tu mor acid ity or ex erts it self a pro metasta tic ac tiv ity re mains to be fully elu ci dated; yet, tu mor lac tate map ping re vealed a lack of cor re la tion with pHe map ping [177], sug gest ing that pHe alone fails to ex plain why high lev els of lac tate are re lated to poor out come. As lac tate it self di rectly pro motes HIF sig nal ing [178,179], an gio gen e sis and tu mor pro gres sion [180,181], fu ture stud ies should be aimed to in ves ti gate the di rect role of lac tate in tu mor metas ta sis.…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%
“…It was experimentally induced by depriving cells of glucose in a medium containing no glutamine, pyruvate, lactate or serum, and an equal amount of viable TCs were systematically compared. As models, we used SiHa cells that were previously documented to rely on OXPHOS for energy production 3,8 and HeLa cells known for their ability to switch from a glucose to a glutamine-(i.e., OXPHOS-dependent) fueled metabolism. 18 In a first series of experiments, we observed a dose-dependent increase in MCT1 and CD147 protein expression in SiHa cells cultured during 48 h with decreasing glucose concentrations ( Figure 1a).…”
Section: Glucose Deprivation Stabilizes Mct1 and Cd147 Protein Expresmentioning
confidence: 99%
“…In oxidative TCs and in endothelial cells, it shares with the metabolic lactate pathway the dependency on MCT1 and the need to oxidize lactate into pyruvate, but requires only a low rate of lactate uptake. [6][7][8] While TCs increase their production of vascular endothelial growth factor in response to lactate, 8,9 endothelial cells are triggered to upregulate the expression of vascular endothelial growth factor receptor 2, basic fibroblast growth factor, and interleukin-8, [6][7][8] thus providing several paracrine and autocrine pathways through which lactate induces angiogenesis. Additional activities of lactate in tumors have been reviewed recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation